Manajemen Mutu Pembelajaran di Masa Pandemi: Studi SD Plus Al Hikmah Purwoasri Kediri - Mustajib; Lia Roikhanatus Sa’adah (Journal of Islamic Education Management, 2021)
When the covid-19 pandemic comes, conventional learning methods must change with online learning methods or commonly called online learning which utilizes media platforms connected to the internet network to distribute materials and communicate between teachers and learners. Even in the event of a covid-19 pandemic learning must still be carried out and cannot be abandoned. Because this kind of learning has never been practiced before, then there are difficulties or problems very potentially arise. To solve this kind of thing, a strategy is needed to solve the problem. The media used must also be considered and adjusted to the conditions of the learners. This activity aims to maintain the quality of learning during the covid-19 pandemic. Even if the learning runs in the network, the quality of learning must still be considered so that the learning runs well and is effectively accepted by learners. This research aims to find out how online learning is done by SD Plus Al Hikmah and how the methods and strategies applied to maintain the quality of online learning so that the learning carried out can run effectively.